Mycobacterium chelonae Keratitis following Keratorefractive Lenticule Extraction: Highlighting Diagnostic and Treatment Complexities - Natalie Elizabeth Allen; Sarah Sarah; Sally Roberts; Stephen R. Ritchie; Alexandra Z. Crawford; Bia Kim (Case Reports in Ophthalmology)
Introduction: This is a rare case of Mycobacterium chelonae keratitis following keratorefractive lenticule extraction (KLEX). Case Presentation: A 35-year-old female presented to the emergency eye clinic with 4 days of eye pain and decreased vision following KLEX surgery. She was using topical tobramycin drops four times per day, which was changed to ciprofloxacin drops. Following initial improvement, the eye deteriorated with further stromal infiltrates. A corneal culture identified M. chelonae. The keratitis required extensive topical and systemic medications, repeat scrapes, and an amniotic membrane over several weeks to reach quiescence. Vision deteriorated to hand movements, but an emergency keratoplasty was avoided. Conclusion: This is the third reported case serving to highlight the diagnostic and treatment challenges associated with postoperative keratitis involving nontuberculous mycobacteria.